Multi-religious families: An implementation of religious moderation based on local wisdom in Central Kalimantan Society - Hamdanah, Hamdanah; Hartati, Zainap; Afifah, Neela; Hilmatunnisa, Hilmatunnisa (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
One interesting social reality in Central Kalimantan society is interfaith marriages, so religious diversity occurs in families. This research aims to examine religious diversity in a family related to the religious practices of each religion and the religious values ​​ built into everyday life. The research method used was qualitative, with a case study approach on families of different religions in the Central Kalimantan region. The subjects of this research were 5 families: 3 families from Danau Pantau Village, Kapuas Regency, and 2 families from Antang Kalang Village, East Kotawaringin Regency, while the data collection technique used observation, interviews, and documentation. The results of this research are as follows: 1) Interfaith families in Central Kalimantan find it easier to implement religious moderation. This means that the majority of people in Danau Pantau village and Tumbang Kalang village easily change religions because of marriage. 2) Implementation of the value of religious moderation in families of different religions in Central Kalimantan in worship: Worship is carried out according to each religion in a safe, harmonious, and peaceful manner. 3) Implementation of the values ​​of religious moderation in families of different religions in Central Kalimantan in the social sector: Implementation of social activities is carried out in a safe, harmonious, and peaceful manner, without distinction of religion or ethnicity.